2021
DOI: 10.1002/pat.5352
|View full text |Cite
|
Sign up to set email alerts
|

Imidazolium‐based poly(ionic liquid)s for demulsification of water in crude oil emulsions

Abstract: Imidazolium‐based ionic liquids (ILs) and their corresponding poly(ionic liquid)s (PILs) as powerful demulsifiers for water separation from the crude oil emulsions were used. Vinyl imidazolium‐based ILs were prepared and then polymerized according to the free radical homo‐polymerization. NMR and FT‐IR analyses confirmed the successful synthesis of ILs and their corresponding polymers. Demulsifying properties of different synthetic ILs, including [C12‐VIM][Br], [C10‐VIM][Br], [C8‐VIM][Br], [C6‐VIM][Br], [C4‐VIM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…With the alkyl chain of 3‐substituents on imidazolium increased from n ‐ethyl, n ‐butyl, n ‐hex1yl to n ‐octyl, the demulsification efficiencies of ILs were increased from 9%, 18%, 96% to 99%. It has been reported that the interfacial tension of ILs decreased when the chain length of ILs increased from n ‐butyl, n ‐hex1yl to n ‐octyl 31 and the diminution of interfacial tension promoted the migration of surfactant species to the interface 44 . These might be due to the ILs with longer alkyl chain have higher affinity to migrate to the interface, displace the surfactants and eventually destabilize the stability of emulsion 45 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…With the alkyl chain of 3‐substituents on imidazolium increased from n ‐ethyl, n ‐butyl, n ‐hex1yl to n ‐octyl, the demulsification efficiencies of ILs were increased from 9%, 18%, 96% to 99%. It has been reported that the interfacial tension of ILs decreased when the chain length of ILs increased from n ‐butyl, n ‐hex1yl to n ‐octyl 31 and the diminution of interfacial tension promoted the migration of surfactant species to the interface 44 . These might be due to the ILs with longer alkyl chain have higher affinity to migrate to the interface, displace the surfactants and eventually destabilize the stability of emulsion 45 …”
Section: Resultsmentioning
confidence: 99%
“…PILs based on ammonium 25–28 and imidazolium 29 were used for demulsification of crude oil emulsions. Ezzat et al 30 and Ebrahim et al 31 found that PILs had better demulsification efficiency than their monomeric ionic liquids under the identical experimental conditions. These PILs were linear polymers and dissolved in the water, making them impossible to be recycled after demulsification.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…It is known that metallic sulfides can reduce the energy of the C–S and C–N in heteroatoms of sulfur and nitrogen which, in turn, have been identified as the main contributors to high viscosity of heavy crude oil streams. Including a small portion of metals in the catalyst may be sufficient to produce a notable reduction in the viscosity of heavy hydrocarbon streams …”
Section: Resultsmentioning
confidence: 99%